The Link between Allergic Rhinitis and Asthma: A Role for Antileukotrienes? - H Kim; J Bouchard; PM Renzix (Canadian Respiratory Journal)
Allergic rhinitis and asthma are both chronic heterogeneous disorders, with an overlapping epidemiology of prevalence, health care costs and social costs in quality of life. Both are inflammatory disorders with a similar pathophysiology, and both share some treatment approaches. However, each disorder has an array of treatments used separately in controlling these atopic disorders, from inhaled corticosteroids, beta2-agonists and antihistamines to newer monoclonal antibody-based treatments. The present article reviews the shared components of allergic rhinitis and asthma, and examines recent evidence supporting antileukotrienes as effective agents in reducing the symptoms of both diseases.